2014
DOI: 10.1002/eco.1592
|View full text |Cite
|
Sign up to set email alerts
|

Assessing CO2 sink/source strength of a degraded temperate peatland: atmospheric and hydrological drivers and responses to extreme events

Abstract: Monthly mean sink/source strength pattern of a degraded temperate peatland in northwestern Turkey was quantified using the eddy covariance technique between July 2010 and February 2014. Atmospheric and hydrological drivers and responses to extreme events of sink/source strength were analysed using multiple linear regression models, support vector machine, multilayer perceptron with principal component analysis and multiple comparisons following general linear models. On the basis of the three full‐year measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
2
0
2
Order By: Relevance
“…Yeniçağa torf yatakları bakımından zengindir ve esas olarak nemli, soğuk ve besin açısından fakir koşullar altında, yeraltı suyunun etkisi olmaksızın oluşan bitkilerin lifli kalıntılarından oluşur. Akı kulesi 2010 yılında 2x2 km²lik bir turbalık üzerine kurulmuştur ve burada faaliyetlerini 2014 yılına kadar sürdürmüştür (Evrendilek, 2015). Şekil 2'de akı kulesinin çalışma alanı içerisindeki konumu yer almaktadır.…”
Section: çAlışma Alanıunclassified
See 1 more Smart Citation
“…Yeniçağa torf yatakları bakımından zengindir ve esas olarak nemli, soğuk ve besin açısından fakir koşullar altında, yeraltı suyunun etkisi olmaksızın oluşan bitkilerin lifli kalıntılarından oluşur. Akı kulesi 2010 yılında 2x2 km²lik bir turbalık üzerine kurulmuştur ve burada faaliyetlerini 2014 yılına kadar sürdürmüştür (Evrendilek, 2015). Şekil 2'de akı kulesinin çalışma alanı içerisindeki konumu yer almaktadır.…”
Section: çAlışma Alanıunclassified
“…Akı kulesi karbon akısı toplamak amacıyla kurulduğu için toprak plakası içermemektedir. Bundan dolayı akı kulesinde Denklem (1)'de verilen terimlerden H, LE ve Rnet değişkenleri için gözlem toplanmasına rağmen G değişkeni için gözlem toplanmamıştır (Evrendilek, 2015). Ancak, ECOR sisteminde G, H, LE ve Rnet farklı sensörler ile birbirinden bağımsız toplanmaktadır.…”
Section: Yersel Verilerunclassified
“…Despite the significant ecosystem services provided by peatlands, it is estimated that 15-20% of their global extent has experienced degradation processes due to anthropogenic disturbances (Joosten, 2009;Joosten & Clarke, 2002;Ma et al, 2022;Parish et al, 2008;Urák et al, 2017;Waddington et al, 2015), generating 5-10% of annual global anthropogenic CO 2 emissions (Friedlingstein et al, 2014;Loisel & Gallego-Sala, 2022). Human pressures have transformed the biogeochemical functionality of peatlands from a C sink in the long term to CO 2 emitters in the short term (Evrendilek, 2014;Munir et al, 2015;Page et al, 2022). Anthropogenic disturbances that directly affect Sphagnum mosses are related to drainage, commercial extraction, or removal of the moss as donor plant material for restoration of degraded peatlands, which have the potential to affect their ecological functionality and modify C dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Dou et al [22] used the ANN method to map different carbon and water fluxes in three Douglas-fir Stands in the Pacific Northwest based on long-term measurements and found that the use of ANN could be effective to determine the responses of three different carbon fluxes (GPP, R and NEE), evapotranspiration and water use efficiency to nitrogen fertilization. Evrendilek [23] compared the three different data-driven methods, including multiple linear regression, ANN and SVM, to estimate the influences of both atmospheric and hydrological drivers on monthly NEE using three years of measurements at a peatland site in northwestern Turkey and obtained satisfactory predictive accuracy.…”
Section: Introductionmentioning
confidence: 99%